Cultural competence and associated factors among nurses working in public health institutions in the Assosa zone, Benishangul Gumuz regional state, Ethiopia, 2022 - Mulualem Birhanu; Asmamaw Getnet; Girma Alem (BMC, 2023)
Abstract Background Cultural competence is one of the principal foundations of clinical nursing. In Ethiopia, nurses in nursing care still focus more on physical needs, the healing process, and treatment and less on the cultural aspects of the patient. Objective This study aims to assess the cultural competence and associated factors among nurses working in public health institutions found in the Assosa Zone, West Ethiopia, in 2022. Methods An institution-based cross-sectional study design was conducted on 362 nurses who were selected by simple random sampling. Data was collected using a structured, self-administered English version of the Nurse Cultural Competence Scale Questionnaire for Nurses. The data were entered into Epi Data version 3.1 and exported to SPSS version 25. Linear regression analysis was used to identify factors statistically significantly associated with the cultural competence of nurses at a p-value < 0.05. Result Overall The mean score of cultural competence of participants was 113 (CI, 111.7-115.7), with a mean item score of 3.2 (CI, 3.15-3.26). Nurse-to-patient ratio (B;.93, CI;.59_1.3), experience with previously working in a primary hospital than the current health institution (B; -11.1, CI; -18_-4.2), and experience with previously working in a health center than the current health institution (B; -11.5, C;-18.5_-4.8), being diploma education level (B; -23.2, CL;-32_-14.8), being BSC education level (B;-20.3, CI;-28_-12.3), and the presence of a feedback system in a health facility (B; 13.5, CI; 9.5_17.5) were identified as predicted factors of cultural competences. Conclusion The overall mean score of the cultural competencies of the participants was moderate. To improve the cultural competence of nurses, it is typically necessary to provide educational opportunities to raise their educational level and establish a feedback system in all health institutions across the nation.